Direct and indirect costs of dental trauma in Sweden: a 2-year prospective study of children and adolescents - Glendor U, Jonsson D, Halling A, Lindqvist K (Blackwell Synergy, 2001)
To study total costs, including direct costs (health care service, loss of personal property, medicine and transport) and indirect costs (loss of production or leisure) of dental trauma to children and adolescents with special reference to predictors.